2020
DOI: 10.3390/ijerph17176203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progressive Resistance Training on Cognition and IGF-1 Levels in Elder Women Who Live in Areas with High Air Pollution

Abstract: The aim of this study was to determine the effects of a muscular strength programme on the levels of insulin-like growth factor-1 (IGF-1) and cognitive status in elder women with mild cognitive impairment who lived in areas of high air pollution. A total of 157 women participated in the study, distributed in four groups: Active/Clean (AC n = 38) and Active/Pollution (AP n = 37), who carried out a progressive resistance training programme for 24 months, and Sedentary/Clean (SC n = 40) and Sedentary/Pollution (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…A growing number of studies have proved that exercise induces considerable physiological changes in the immune system (Hoffman-Goetz and Pedersen, 1994 ; Nieman, 1997 ; Gleeson and Pyne, 2000 ; Pedersen and Hoffman-Goetz, 2000 ). Cytokines (IL-6, IL-8, IL-10, and TNF-α) (Normando et al, 2013 ; Bos et al, 2014 ; Lu et al, 2015a ; Trnjar et al, 2017 ), inflammation-relate proteins (CRP, FeNO, CC16, CD62P, CD63, and CD40) (Rundell et al, 2007 ; Cutrufello et al, 2011 ; Normando et al, 2013 ; Trnjar et al, 2017 ), and stress hormones (including epinephrine, norepinephrine, growth hormone, b-endorphins, insulin, and cortisol) (Volek et al, 1997 ; Molina-Sotomayor et al, 2020 ) are most common indexes to estimate the variety of immune function influenced by exercise. As for the duration of the study, in view of the potential ethical approval difficulties of long-term air pollution exposure, most of the existing studies focus on the impacts of exercise and physical activities in short-term exposure to the body.…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of studies have proved that exercise induces considerable physiological changes in the immune system (Hoffman-Goetz and Pedersen, 1994 ; Nieman, 1997 ; Gleeson and Pyne, 2000 ; Pedersen and Hoffman-Goetz, 2000 ). Cytokines (IL-6, IL-8, IL-10, and TNF-α) (Normando et al, 2013 ; Bos et al, 2014 ; Lu et al, 2015a ; Trnjar et al, 2017 ), inflammation-relate proteins (CRP, FeNO, CC16, CD62P, CD63, and CD40) (Rundell et al, 2007 ; Cutrufello et al, 2011 ; Normando et al, 2013 ; Trnjar et al, 2017 ), and stress hormones (including epinephrine, norepinephrine, growth hormone, b-endorphins, insulin, and cortisol) (Volek et al, 1997 ; Molina-Sotomayor et al, 2020 ) are most common indexes to estimate the variety of immune function influenced by exercise. As for the duration of the study, in view of the potential ethical approval difficulties of long-term air pollution exposure, most of the existing studies focus on the impacts of exercise and physical activities in short-term exposure to the body.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a transient increase in serum BDNF following resistance exercise in older adults could have implications for improved cognitive function in older adults. In this sense, resistance training has been correlated with increased serum levels of insulin-like growth factor1 (IGF-1) [4,58], which is an essential factor in brain neurogenesis and cognitive function [59]. Similarly, myokines are produced following skeletal muscle contractions and exert autocrine, paracrine, and endocrine effects which are sensed by the brain and may lead to changes in plasticity [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, oxidative stress increases age-related brain deterioration [2], with a decrease of executive functions [3]. However, it has been demonstrated that a progressive, low-to-moderateintensity, individualized, and controlled resistance training programme produces significant improvements in maximum muscle strength and cognition in older women [4]. In this sense, it has been reported that the decrease of muscle strength, regardless of muscle mass, could be considered as the core of fragility, as it can predict changes in gait speed Sustainability 2021, 13, 7687 2 of 15 and mobility and involves greater risk of mortality in older people [5].…”
Section: Introductionmentioning
confidence: 99%
“…This can be avoided or mitigated by endogenous biological mechanisms such as the generation of IGF-1, which is induced by resistance training. In addition, Franco Martin et al [ 40 ] suggest that “physical activity is being recognized as a highly protective factor, and it has been established today [ 41 ] as a promising psychosocial strategy for the protection of cognitive faculties”.…”
Section: Discussionmentioning
confidence: 99%